Metode Eklektik dalam Pembelajaran Bahasa Arab di Pesantren: Antara Tradisi dan Modernitas - Ramdani Nopandri; Mely Rahmadani (ALSYS, 2026)
Although the use of various teaching methods in Arabic language learning has been widely examined, research specifically discussing the systematic application of the eclectic method (thariqah intiqaiyyah) in pesantren contexts, where traditional and modern educational values intersect, remains limited. This study aims to examine the conceptual foundations, implementation patterns, and effectiveness of the eclectic method in Arabic language learning in Islamic boarding schools in Indonesia. This study used a qualitative approach with a library research design through the analysis of primary and secondary sources, including journal articles, institutional reports, and relevant academic literature published during the 2020–2025 period. Data were collected through systematic documentation and analyzed using content analysis techniques with descriptive-interpretive elaboration. The findings show that the eclectic method enables pesantren educators to selectively integrate elements from various established methods, such as the grammar-translation method, the direct method, and the communicative approach, to address the diverse needs of learners and the dynamics of the learning context. This finding contributes to the development of integrative language pedagogy and broadens understanding of adaptive Arabic language teaching practices in Islamic educational institutions. The study concludes that methodological flexibility plays an important role in maintaining the dual mission of pesantren as preservers of classical Islamic tradition and agents of educational modernization. The implications of this study include theoretical contributions to the development of integrative Arabic language pedagogy and practical implications for pesantren educators and curriculum developers in designing context-sensitive and learner-centered Arabic language learning.